Vitamin D handbook : (Wiley-Interscience, 2008)
This hands-on, comprehensive reference provides accessible, organized information on the structures and applications of Vitamin D and its related chemicals. The most extensive published list of Vitamin D molecules, it provides a record for approximately 950 derivatives of Vitamins D2 and D3.